2012
DOI: 10.1021/cr2004508
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Manganese Oxide Nanocrystals: Fabrication, Characterization, and Microstructure

Abstract: Nanocrystals 3835 3.1. Progress in Mn 2 O 3 Nanomaterials 3835 3.2. Synthesis of Mn 2 O 3 Nanocrystals 3836 3.2.1. Method 3836 3.2.2. Instrumental Analysis 3836 3.3. Grain Growth Kinetics of Mn 2 O 3 Nanocrystals 3836 3.3.1. Kinetic Analysis 3836 3.3.2. Microstructure Analysis 3838 3.4. Spectral Properties of Mn 2 O 3 Nanocrystals 3839 3.4.1. Raman Features of Different Grain Sizes 3839 3.4.2. IR Features of Different Grain Sizes 3840 3.4.3. XPS Analysis of Different Grain Sizes 3841 3.4.4. ESR Analysis of Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
163
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(167 citation statements)
references
References 192 publications
2
163
0
Order By: Relevance
“…MnO x nanocomposites have attracted increasing attention in photocatalysis, energy storage, and Li ion batteries because of their low cost, environmental abundance, and high theoretical specific capacitances. 4,5 Recently, several research groups have reported that graphene-supported MnO x nanocomposites can play a critical role in energy storage [5][6][7] and can be prepared by using an aqueous chemical method, 8 chemical reduction, [9][10][11] and colloidal mixing. 12 However, these methods are somewhat complicated and require different synthetic protocols to prepare specific MnO x nanoparticles (NPs) on graphene, which makes it difficult to produce those nanocomposites.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…MnO x nanocomposites have attracted increasing attention in photocatalysis, energy storage, and Li ion batteries because of their low cost, environmental abundance, and high theoretical specific capacitances. 4,5 Recently, several research groups have reported that graphene-supported MnO x nanocomposites can play a critical role in energy storage [5][6][7] and can be prepared by using an aqueous chemical method, 8 chemical reduction, [9][10][11] and colloidal mixing. 12 However, these methods are somewhat complicated and require different synthetic protocols to prepare specific MnO x nanoparticles (NPs) on graphene, which makes it difficult to produce those nanocomposites.…”
Section: -3mentioning
confidence: 99%
“…4 For the synthesis of MnO/G and Mn 3 O 4 /G, GO (0.2 g) was mixed with Mn(CH 3 COO) 2 ·4H 2 O (0.89 g) in 200 mL of distilled water. Hydrazine monohydrate (5 mL, 80%) was added to the mixture and stirred for 24 h to promote the intercalation of Mn 2+ on the GO.…”
Section: +mentioning
confidence: 99%
“…Among the transition metals, manganese exhibits several oxidation state and forms different oxides such as MnO [8,9], Mn 2 O 3 [10,11], Mn 3 O 4 [8][9][10][11], and MnO 2 [8]. Manganese oxides are an important class of transition metal oxide family due to unique chemical and physical properties [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Among the transition metals, manganese exhibits several oxidation state and forms different oxides such as MnO [8,9], Mn 2 O 3 [10,11], Mn 3 O 4 [8][9][10][11], and MnO 2 [8]. Manganese oxides are an important class of transition metal oxide family due to unique chemical and physical properties [8][9][10][11]. Among the different oxidation state of manganese oxides, Mn 2 O 3 nanoparticles are well-known as non-toxic, cheap, environmentally friendly and abundant and widely investigated as anode materials for lithium ion batteries because of their large theoretical specific capacities [12][13][14], catalyst [15,16] and hydrazine electrochemical sensing [17].…”
Section: Introductionmentioning
confidence: 99%
“…1 Among them, manganese-based oxides in the form of ultra-fine particles and thin-film hetero-structures have found a number of applications where the surface and interface properties are significant. 2,3 Their catalytic behavior, magnetic properties, and ability to form large linked complexes with cyanide and ammonium ions make them important class of compounds.…”
Section: Introductionmentioning
confidence: 99%